Hydrogel and polypeptide-based synergistic anti-pollution electrochemical sensor, preparation method and application thereof
Patent Information
- Application Number
- CN202611076950.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在复杂生物样本中,传感界面易受到蛋白质、细胞碎片及其他生物大分子的非特异性吸附,导致界面电子传递受阻以及检测灵敏度下降,从而严重影响传感器检测的准确性和稳定性
聚丙烯酰胺(PAM)是一种高亲水性聚合物,富含酰胺官能团,使其在抗污染界面构建中展现出良好的应用前景。其极性酰胺基团与周围水分子发生强相互作用,形成致密的界面水合层,有效抑制生物污染物的非特异性吸附,赋予材料优异的抗污染性能。此外,当进一步交联形成水凝胶后,仍能保持其固有的亲水性,并通过高度水合的网络结构增强水合层的稳定性。然而,这种致密的水合层和PAM水凝胶的绝缘特性会阻碍电子转移,而紧密结合的水分子则增加了氧化还原探针向电极表面扩散的阻力,导致信号传导效率下降。因此,将PAM水凝胶中引入导电组分,对于平衡抗污染性能与导电性至关重要。
Smart Images

Figure CN122983145A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical analysis technology, and relates to a synergistic anti-fouling electrochemical biosensor based on liquid metal composite hydrogel and multifunctional peptide, its preparation method and application. Specifically, it discloses an electrochemical biosensor with excellent anti-fouling performance and high sensitivity for the detection of interleukin-1β in saliva. Background Technology
[0002] With the rapid development of personalized medicine and precision diagnostics, the demand for rapid, sensitive, and highly sensitive quantitative analysis of trace biomarkers has increased dramatically. As a typical non-invasive bodily fluid, saliva has received widespread attention in the field of disease diagnosis due to its advantages such as convenient collection, high safety, low cost, and ease of continuous monitoring. In recent years, increasing research has shown that saliva contains abundant biomarkers, including proteins, nucleic acids, and exosomes, and abnormal changes in their concentrations are closely related to various diseases such as lung cancer, breast cancer, and inflammatory diseases. Interleukin-1β (IL-1β), a typical pro-inflammatory cytokine, is mainly secreted by macrophages, monocytes, and epithelial cells, playing a crucial role in regulating inflammatory responses, immune responses, and cell signaling. When encountering infection, tissue damage, or autoimmune attack, IL-1β is rapidly generated, thereby enhancing and maintaining the inflammatory response. Abnormal expression of IL-1β is closely related to various pathological processes, such as inflammatory diseases, autoimmune diseases, and cancer. Furthermore, IL-1β is an important inflammatory biomarker in saliva, secreted by salivary glands and oral mucosal cells. Changes in its concentration can reflect local and systemic inflammatory states. Therefore, developing a highly sensitive salivary IL-1β detection platform is of great significance for early diagnosis and real-time monitoring.
[0003] In recent years, an increasing number of studies have demonstrated the significant advantages of electrochemical biosensors in the detection of trace biomarkers, primarily due to their high sensitivity, rapid response, low cost, and ease of operation. Especially in the early stages of disease, biomarkers are often present at trace levels, with concentrations frequently below the effective detection range of traditional analytical methods. Through efficient interfacial electron transfer, electrochemical biosensors can achieve sensitive identification and ultra-low-limit detection of trace target molecules, thus showing broad application prospects in early disease screening and dynamic monitoring. However, in complex biological samples, the sensing interface is susceptible to non-specific adsorption by proteins, cell debris, and other biomolecules, leading to impaired interfacial electron transfer and decreased detection sensitivity, thereby severely affecting the accuracy and stability of sensor detection.
[0004] Therefore, constructing interfaces with excellent anti-fouling properties has become a key strategy for improving the accuracy and reliability of electrochemical biosensors in complex biological environments. Summary of the Invention
[0005] In view of this, the present invention proposes an electrochemical sensor based on a hydrogel and peptide synergistic antifouling mechanism and its preparation method. By constructing a synergistic antifouling interface, non-specific adsorption in complex saliva matrices is effectively suppressed. At the same time, the conductivity of the sensing interface is improved, thereby enhancing the sensitivity and accuracy of IL-1β detection.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The present invention first provides an electrochemical sensor based on hydrogel and peptide synergistic antifouling. The electrochemical sensor is constructed by stepwise assembly. First, a poly(3,4-ethylenedioxythiophene) film is deposited on the surface of a glassy carbon electrode. Then, an LM@CNC-PAM-CS hydrogel suspension is drop-coated onto the poly(3,4-ethylenedioxythiophene) film to form a functionalized hydrogel interface. Finally, a peptide is coupled to the functionalized hydrogel interface to obtain the electrochemical sensor based on hydrogel and peptide synergistic antifouling.
[0007] Furthermore, the preparation method of the LM@CNC-PAM-CS hydrogel suspension is as follows:
[0008] 100 mg of liquid metal was added to 2 mL of a 0.2 wt% aqueous solution of cellulose nanofibers, and the mixture was sonicated in an ice-water bath for 30 minutes to obtain a uniformly dispersed LM@CNC nanoparticle suspension. Subsequently, chitosan was dissolved in 1% acetic acid to prepare a 2 mg / mL solution. -1 A chitosan solution was prepared; then, 1.5 g of acrylamide was added to the LM@CNC nanoparticle suspension and sonicated for 20 minutes; then the prepared chitosan solution was added and sonicated for another 20 minutes to obtain an LM@CNC-PAM-CS hydrogel suspension; the liquid metal was composed of 75% Ga and 25% In.
[0009] Furthermore, the amino acid sequence of the polypeptide is: CPPPPKSESKSENFMQGTSYHHVY, wherein the anchoring sequence is CPPPP, the anti-pollution sequence is KSESKSE, and the specific recognition sequence for IL-1β is NFMQGTSYHHVY.
[0010] Its beneficial effects are as follows: Polyacrylamide (PAM) is a highly hydrophilic polymer rich in amide functional groups, making it a promising candidate for constructing antifouling interfaces. Its polar amide groups interact strongly with surrounding water molecules to form a dense interfacial hydration layer, effectively inhibiting the non-specific adsorption of biopollutants and endowing the material with excellent antifouling properties. Furthermore, when further crosslinked to form a hydrogel, it retains its inherent hydrophilicity and enhances the stability of the hydration layer through a highly hydrated network structure. However, this dense hydration layer and the insulating properties of the PAM hydrogel hinder electron transfer, while the tightly bound water molecules increase the resistance to the diffusion of redox probes to the electrode surface, leading to a decrease in signal transduction efficiency. Therefore, introducing conductive components into the PAM hydrogel is crucial for balancing antifouling performance and conductivity.
[0011] Liquid metals (LMs), especially gallium-based liquid metals, have shown great potential in biomedicine, microfluidic electronics, and biosensing due to their excellent conductivity, unique fluidity, good biocompatibility, and low toxicity. Compared with traditional solid conductive fillers, LMs can not only form continuous conductive channels but also dynamically adapt to changes in the internal structure of hydrogels, thereby alleviating internal stress at the interface and making them ideal conductive fillers for constructing hydrogels. However, the high surface tension of LMs leads to poor dispersion stability and a tendency for spontaneous aggregation, which in turn affects their uniform distribution and interfacial interactions. To address this issue, this invention introduces cellulose nanocrystals (CNCs) as an interfacial stabilizer. With their excellent biocompatibility, high specific surface area, and abundant surface hydroxyl and carboxyl groups, CNCs can be stably adsorbed onto the surface of LM droplets through coordination interactions, significantly improving their dispersibility. Simultaneously, CNCs can also form hydrogen bonds with polymer chains, thereby promoting the structural stability of the hydrogel. Under ultrasonication, CNC-stabilized liquid metal nanodroplets (LM@CNC) can generate a large number of free radicals and Ga... 3+ These substances can initiate the rapid polymerization of vinyl monomers to form hydrogels without the need for additional traditional initiators or crosslinking agents. Therefore, the free radicals and Ga in LM@CNC... 3+ The rapid polymerization of acrylamide monomers can be triggered to generate PAM hydrogel. Chitosan (CS) is then introduced, utilizing its hydrogen bonding with LM@CNC and PAM chains to further enhance network stability and provide abundant active amino sites for subsequent biomolecule immobilization. Ultimately, this invention prepares a multifunctional composite hydrogel (LM@CNC-PAM-CS) that combines antifouling properties with conductivity.
[0012] However, it is worth noting that while the introduction of LM@CNC significantly improves the conductivity of the hydrogel, it may weaken the compactness of the antifouling interface to some extent. To address this, this invention integrates different antifouling materials to construct a synergistic antifouling interface. Compared to other antifouling materials, peptides possess significant advantages such as sequence programmability, structural diversity, and excellent biocompatibility. By regulating the composition and arrangement of amino acids, peptides can simultaneously endow the interface with multiple functions, including antifouling properties, molecular recognition, antibacterial activity, and interface anchoring. In particular, zwitterionic peptides, composed of equal amounts of positively and negatively charged amino acid residues, achieve overall charge neutrality, minimizing non-specific electrostatic interactions with biopollutants. Simultaneously, they effectively inhibit non-specific adsorption by binding water molecules to form a stable hydration layer. Furthermore, by inserting hydrophilic serine (Ser) intervals into the zwitterionic (KE) sequence, while preserving the original electrostatic balance and hydration, the hydrophilic side chains enhance the hydration capacity of the interface, thereby significantly improving the antifouling performance of the peptides.
[0013] This invention also provides a method for preparing the above-described electrochemical sensor based on hydrogel and peptide synergistic antifouling, comprising the following steps: (1) Polish the glass carbon electrode with Al2O3 powder, and then use deionized water and anhydrous ethanol for ultrasonic cleaning to remove adsorbed impurities; (2) A poly(3,4-ethylenedioxythiophene) thin film was formed on the surface of a glassy carbon electrode by electrochemical deposition. (3) The LM@CNC-PAM-CS hydrogel suspension was drop-coated onto the surface of a poly(3,4-ethylenedioxythiophene) film and incubated to obtain an LM@CNC-PAM-CS hydrogel modified electrode. Then, it was immersed in PBS buffer to allow the hydrogel to fully swell to equilibrium and obtain a functionalized hydrogel interface. (4) The functionalized hydrogel interface was immersed in a solution of sulfosuccinimide-4-(N-maleimidemethyl)cyclohexane-1-carboxylic acid ester and reacted. After the reaction was completed, it was thoroughly washed with water to remove residual reagents. (5) Finally, a polypeptide solution was added to the washed interface surface and incubated to obtain the antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE, which is the hydrogel and polypeptide synergistic antifouling electrochemical sensor.
[0014] Preferably, the electrochemical deposition method in step (2) to form a poly(3,4-ethylenedioxythiophene) film on the surface of the glassy carbon electrode specifically involves: using an electrochemical polymerization solution composed of 0.01 mg of poly(sodium 4-styrene sulfonate) and 10 mM of 3,4-ethylenediol thiophene, and depositing it at 1.0 V in amperometric mode for 20 seconds to form a poly(3,4-ethylenedioxythiophene) film on the surface of the glassy carbon electrode.
[0015] Preferably, the volume of the LM@CNC-PAM-CS hydrogel suspension used in step (3) is 3.0 μL; the incubation time is 2 h; and the pH of the PBS buffer is 7.4 and the concentration is 10 mM.
[0016] Preferably, the amount of SMCC solution used in step (4) is 10 μL, the concentration is 2.0 mM, and the reaction time is 1 h.
[0017] Preferably, the amount of polypeptide solution used in step (5) is 10 μL, and the concentration is 0.2 mg / mL. -1 The incubation time is 2 hours.
[0018] This invention also provides an application of the above-mentioned electrochemical sensor based on hydrogel and peptide synergistic antifouling. Specifically, the application is the detection of IL-1β in complex biological environments; the complex biological environment is preferably human saliva.
[0019] This invention provides an electrochemical sensor based on the synergistic antifouling effect of hydrogels and peptides, its preparation method, and its application. Compared with existing technologies, it has the following advantages: (1) The present invention utilizes PAM hydrogel, which contains abundant amide groups. These polar groups interact strongly with the surrounding water molecules to form a dense interfacial hydration layer, effectively inhibiting non-specific adsorption in complex biological samples and significantly improving the anti-fouling ability of the sensing interface.
[0020] (2) By constructing a composite interface that combines conductivity and anti-fouling properties, the present invention maintains excellent electron transport capability while ensuring anti-fouling performance, thereby improving the detection sensitivity of target objects.
[0021] (3) The multifunctional polypeptide designed in this invention contains an anchoring sequence, which anchors the polypeptide to the electrode at the hydrogel-modified interface. The antifouling sequence balances opposite charges and forms a stable hydration layer, achieving neutrality through hydration and charge, thereby minimizing the adsorption of non-specific proteins. The recognition sequence achieves specific binding to IL-1β by providing complementary chemical functions and spatial conformations.
[0022] (4) The method for synthesizing hydrogels in this invention is simple, has good biocompatibility and low toxicity, and does not require the addition of initiators and crosslinking agents. The prepared sensor has good biocompatibility and can detect target substances in complex biological samples, and has good clinical detection and application prospects. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0024] Figure 1 A schematic diagram of the fabrication of an LM@CNC-PAM-CS hydrogel and a peptide electrochemical biosensor.
[0025] Figure 2 SEM images of LM@CNC particles: (A) 500 nm scale bar, (B) 100 nm scale bar. (C) XPS spectrum of LM@CNC droplets. (D) Ga... 3d and (E) Ga 2p XPS region. (F) XPS spectrum of LM@CNC-PAM-CS hydrogel. (G) SEM image of LM@CNC-PAM-CS hydrogel. (H) FTIR spectral characteristics of the hydrogel. (I) Rheological behavior of the hydrogel in the strain range of 0.01% to 10%.
[0026] Figure 3 (A) Scanning electron microscope image of PEDOT thin film. (B) XPS spectrum of PEDOT-modified surface. (C) Surface composition of PEDOT-modified film containing 0.1 mM KCl and 5 mM [Fe(CN)6]. 3- / 4- In PBS (10 mM, pH 7.4), the DPV current characterized the stepwise construction process of the biosensor.
[0027] Figure 4 (A) Contact angles of GCE, PEDOT / GCE, LM@CNC / PEDOT / GCE, LM@CNC-PAM-CS / PEDOT / GCE, and Pep / LM@CNC-PAM-CS / PEDOT / GCE. Current suppression rates at the electrode interfaces after treatment with different concentrations of (B) BSA, (C) Lys, (D) Muc, and (E) Fib. (F) Fluorescence images of (a) bare electrode, (b) PEDOT, (c) LM@CNC-PAM-CS, and (d) peptide-modified surfaces treated with FITC-BSA.
[0028] Figure 5 Signal inhibition rates of each electrode after soaking in (A) unstimulated saliva and (B) chewing-stimulated saliva at different concentrations. (C) DPV signal inhibition at the hydrogel and peptide-modified interface after 15 days of exposure in 50% human saliva.
[0029] Figure 6 In PBS (A) and 50% unstimulated saliva (B), after background subtraction, different IL-1β concentrations (from 1.0 pg / mL) -1 Up to 1.0 μg mL -1 (C) Linear calibration curves of the biosensor for IL-1β in PBS and 50% unstimulated saliva. (D) Biosensor for 100.0 ng / mL -1 Multiple interfering proteins (IL-6, cTnI, ANXA1, HER2, CRP, and Aβ) 1-42 ) and 100.0 pg mL -1 IL-1β, and the current response of these protein mixtures (Mix). (E) Current changes when detecting IL-1β using a biosensor fabricated with seven independent electrodes. (F) Consistency of the biosensor with the ELISA kit for the analysis of IL-1β in saliva samples. Detailed Implementation
[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] It should be noted that, unless otherwise specified, the experimental methods in the following embodiments are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.
[0032] The materials and reagents used in this invention are as follows: The amino acid sequence of the polypeptide is: CPCPKSESKSENFMQGTSYHHVY, where the anchoring sequence is CPCP, the antifouling sequence is KSESKSE, and the specific recognition sequence for IL-1β is NFMQGTSYHHVY. It was synthesized by Suzhou Modifu Biotechnology Co., Ltd. Liquid metal (LM), composed of 75% Ga and 25% In, was purchased from Shenyang Jiabei Trading Co., Ltd. Cellulose nanofibers (CNC, 3 wt% aqueous dispersion) were from Guilin Qihong Technology Co., Ltd. Acrylamide (AM), 3,4-ethylenediol thiophene (EDOT), N,N'-methylenebisacrylamide (MBA), and poly(sodium 4-styrene sulfonate) (PSS) were provided by Shanghai Aladdin Biochemical Technology Co., Ltd. Chitosan (CS), methylene blue (MB), lysozyme (Lys), mucin (Muc), and fibrinogen (Fib) were provided by Shanghai Mikelin Biochemical Co., Ltd. Interleukin-1β (IL-1β) was purchased from Shanghai Sigma-Aldrich. Ammonium persulfate (APS) and bovine serum albumin (BSA) were purchased from Shanghai Adamas Reagent Co., Ltd. N,N,N',N'-Tetramethylethylenediamine (TEMED) was provided by Beijing Xinke Zhongjing Trading Co., Ltd. FITC-BSA, myoglobin (Mb), C-reactive protein (CRP), and annexin A (ANXA1) labeled with fluorescein isothiocyanate were provided by Beijing Solarbio Science & Technology Co., Ltd. Sulfosuccinimide-4-(N-maleimidemethyl)cyclohexane-1-carboxylic acid ester (sulfo-SMCC) was provided by Shandong Sikejie Biotechnology Co., Ltd. Interleukin-6 (IL-6) was from MedChemExpress. Cardiac troponin I (cTnI) was provided by Shanghai Lingchao Biotechnology Co., Ltd. Amyloid-β... 1-42 (Aβ) 1-42 Human epidermal growth factor receptor-2 (HER2) and other saliva samples were provided by Shanghai Sangon Biotech. Human saliva samples were collected from volunteers using two methods. For non-irritating saliva, participants coughed up saliva naturally into sterile centrifuge tubes every 30 seconds; for irritating saliva, participants chewed gum to stimulate saliva production and coughed it up into sterile centrifuge tubes at 30-second intervals. All experiments used a Milli-Q water purification system to prepare ultrapure water (18 MΩ·cm⁻¹). -1 All chemical substances are analytical grade.
[0033] The instruments used in this invention are as follows: The materials were electrochemically characterized using a Shanghai CHI-660E electrochemical workstation and a standard three-electrode configuration (glassy carbon electrode as working electrode, saturated calomel electrode as reference electrode, and platinum wire as counter electrode), including cyclic voltammetry (CV) and differential pulse voltammetry (DPV).
[0034] The samples were ultrasonicated using a Kunshan KQ218 ultrasonic processor (70 W). To investigate the microstructure and elemental distribution of the sample surface, a Hitachi JSM-75000F scanning electron microscope (SEM) equipped with an energy dispersive spectroscopy (EDS) instrument was used for analysis. X-ray photoelectron spectroscopy (XPS) measurements were performed using a Thermo ESCALAB 250Xi instrument to determine the elemental composition and valence state. Fourier transform infrared (FTIR) spectra were obtained using a Thermo-Nicolet 6700 infrared spectrometer for chemical structure analysis. The viscoelastic properties of the hydrogel were evaluated using a TA Instruments ARES-G2 rheometer. Protein adsorption behavior was observed using a confocal laser scanning microscope (Leica, Germany). Surface wettability was evaluated using a JC2000D1 contact angle meter.
[0035] In this invention, a multifunctional hydrogel is combined with a designed peptide to prepare an anti-fouling electrochemical biosensor for detecting IL-1β in saliva. The synthesis process is as follows ( Figure 1 First, CNC-stabilized liquid metal (LM@CNC) droplets were formed through ultrasonic treatment. Then, AM monomers and CS were added sequentially to synthesize a hydrogel suspension (LM@CNC-PAM-CS). Next, an electrochemical biosensor was constructed through stepwise assembly. Poly(3,4-ethylenedioxythiophene) (PEDOT) was electrodeposited onto the electrode, followed by deposition of the hydrogel suspension droplets (LM@CNC-PAM-CS) onto the electrode surface. To compensate for the adverse effects of conductive materials on the biosensor's antifouling performance, a designed peptide was incubated onto the sensing surface to achieve a synergistic antifouling effect. This peptide binds to the amino groups of the hydrogel through its terminal thiol group, thus forming a synergistic antifouling biosensor. The introduction of the multifunctional peptide improved the antifouling performance of the modified hydrogel electrode, enabling accurate and sensitive detection of IL-1β in complex biological environments.
[0036] Example 1: Preparation of LM@CNC-PAM-CS hydrogel suspension 100 mg of liquid metal (composed of 75% Ga and 25% In) was added to 2 mL of 0.2 wt% cellulose nanofiber (CNC) aqueous solution, and sonicated in an ice-water bath for 30 minutes to obtain a uniformly dispersed LM@CNC nanoparticle suspension; subsequently, chitosan (CS) was dissolved in 1% acetic acid to prepare 2 mg / mL of the solution. -1The chitosan solution was then added; next, 1.5 g of acrylamide (AM) monomer was added to the LM@CNC nanoparticle suspension and sonicated for 20 minutes; then chitosan (CS) solution was added and sonicated for another 20 minutes to obtain the LM@CNC-PAM-CS hydrogel suspension.
[0037] Liquid metals (LMs), especially gallium-based alloys, are highly attractive materials for electrochemical sensing applications due to their high conductivity, low toxicity, excellent chemical stability, and good biocompatibility. However, the low viscosity and high surface tension of liquid metals easily lead to droplet aggregation and poor dispersion stability. Therefore, cellulose nanocrystals (CNCs) are used to maintain the stable dispersion of liquid metals and prevent their aggregation. Stable CNC-stabilized liquid metal (LM@CNC) droplet suspensions can be obtained by ultrasonically treating a mixed suspension of liquid metal and CNCs. This is attributed to the interaction between the hydroxyl (-OH) and carboxyl (-COOH) groups on the CNCs and the Ga... 3+ Coordination between ions. Radical polymerization of AM monomers was initiated using LM@CNC suspension as a medium without the need for additional initiators and crosslinking agents. During ultrasonic treatment, unpaired electrons in the outermost orbitals of Ga react with π electrons in the AM double bond to generate monomer radicals, ultimately initiating the formation of PAM.
[0038] Scanning electron microscopy (SEM) images further revealed that the LM@CNC droplets exhibited uniformly distributed small spherical nanoparticles with relatively rough surfaces and a fibrous structure. Figure 2 A). Notably, several fibrous protrusions were observed on the surface of the LM droplets, and magnified SEM images revealed these to be exposed CNC nanofibers. Figure 2 B). X-ray photoelectron spectroscopy (XPS) analysis showed that LM@CNC exhibited wavelengths corresponding to C at 285.7 eV, 533.1 eV, 20.1 eV, 1118.2 eV, and 446.3 eV, respectively. 1s O 1s Ga 2p Ga 3d and In 3d peak ( Figure 2 C). Among them, Ga 3d The spectrum shows peaks at 18.2 eV and 20.5 eV, corresponding to Ga, respectively. 0 and Ga 3+ ( Figure 2 D); Figure 2 E shows, Ga 2p After peak splitting, the spectrum was at 1116.8 eV (Ga 0 ) and 1119.3 eV (Ga 3+The presence of peaks at these locations indicates that an oxidation reaction occurred on the LM surface, resulting in the formation of Ga. 3+ ion.
[0039] The characteristic N1s peak at 339.2 eV in the XPS spectrum verifies the successful preparation of the LM@CNC-PAM-CS hydrogel. Figure 2 F). To investigate the interactions between chemical groups within the LM@CNC-PAM-CS hydrogel, Fourier transform infrared spectroscopy (FTIR) analysis was performed, such as... Figure 2 As shown in H. Approximately 3342 cm. -1 The broad absorption peak at 3186 cm⁻¹ is attributed to the overlapping stretching vibrations of OH and NH groups in PAM and CS, indicating strong hydrogen bonding within the hydrogel. -1 The absorption peak at 1646 cm⁻¹ corresponds to the stretching vibration of the NH₂ group. Furthermore, the absorption peak at 1646 cm⁻¹... -1 and 1600 cm -1 The characteristic peaks at 1612 cm⁻¹ are attributed to the stretching vibration of the CO bond in PAM, the in-plane bending vibration of NH in -CONH₂, and the bending vibration of NH in CS, respectively. -1 The near-complete disappearance of the characteristic C=C stretching band demonstrates the successful transformation of AM into PAM. Rheological measurements were used to evaluate the network formation and structural stability of LM@CNC-PAM-CS. Figure 2 As shown in Figure I, the storage modulus (G′) of the hydrogel is always higher than the loss modulus (G″) in the strain range of 0.01% to 100%, exhibiting obvious solid viscoelastic behavior, which confirms the formation of a stable hydrogel network.
[0040] Example 2: Construction of an electrochemical sensor based on hydrogel and peptide synergistic antifouling (1) First, the glass carbon electrode (GCE) was polished with Al2O3 powder of 0.3 μm and 0.5 μm in sequence, and then ultrasonically cleaned with deionized water and anhydrous ethanol to remove adsorbed impurities.
[0041] (2) Using electrochemical deposition, prepare 5 mL of electrochemical polymerization solution containing 0.01 mg of poly(sodium 4-styrene sulfonate) (PSS) and 10 mM 3,4-ethylenedioxythiophene (EDOT), and deposit it at 1.0 V in amperometric mode for 20 seconds to form a poly(3,4-ethylenedioxythiophene) film on the surface of a glassy carbon electrode.
[0042] (3) Drop 3.0 μL of the LM@CNC-PAM-CS hydrogel suspension prepared in Example 1 onto the surface of a poly(3,4-ethylenedioxythiophene) film and incubate for 2 h to obtain an LM@CNC-PAM-CS hydrogel modified electrode. Then, immerse it in a PBS buffer solution of pH 7.4 and 10 mM to allow the hydrogel to fully swell to equilibrium and obtain a functionalized hydrogel interface.
[0043] (4) The functionalized hydrogel interface was immersed in 10 μL of 0.2 mM sulfosuccinimide-4-(N-maleimidemethyl)cyclohexane-1-carboxylic acid ester solution and reacted for 1 h. After the reaction was completed, the interface was thoroughly washed with water to remove residual reagents.
[0044] (5) Finally, add 10 μL and 0.2 mg mL of the solution to the washed interface surface. -1 The peptide solution was incubated for 2 h to obtain the antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE.
[0045] SEM is used to characterize the surface morphology of electrodeposited PEDOT films. Figure 3 A) The results showed that it has a uniform particle structure, which can effectively increase the electroactive surface area and promote interfacial electron transfer. XPS analysis further verified the successful electrodeposition of PEDOT on the electrode surface, and S was observed at 164.9 eV, 284.8 eV and 532.3 eV, respectively. 2p C 1s and O 1s Characteristic peaks ( Figure 3 B). Furthermore, the stepwise construction process of the biosensor was examined using DPV measurements. Figure 3 C). Compared to glassy carbon electrode (GCE), PEDOT electrodeposition significantly improved the peak current, thanks to its superior conductivity and larger electroactive surface area. With sequential immobilization of LM@CNC-PAM-CS hydrogel and peptides, the current response gradually decreased, as the modification with low-conductivity biomolecules hindered electron transfer. Finally, subsequent incubation with IL-1β resulted in a further decrease in current, confirming the successful fabrication of the biosensor. Notably, the significantly lower current response of PAM / PEDOT / GCE compared to LM@CNC-PAM-CS hydrogel highlights the crucial role of LM in enhancing conductivity.
[0046] Example 3: Antifouling characterization of the antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE The antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE prepared in this invention has synergistic antifouling properties between the LM@CNC-PAM-CS hydrogel and the designed peptide-modified interface. Its core lies in the formation of a stable hydration layer, thereby inhibiting the adsorption of non-specific proteins in complex biological fluids.
[0047] To evaluate the hydrophilicity of different surfaces, the contact angles (WCAs) of each surface were measured. For example... Figure 4 As shown in Figure A, the contact angle of the bare GCE was 63.94°, while the contact angles of the PEDOT and LM@CNC modified electrodes decreased to 46.21° and 33.49°, respectively. After sequential peptide modification of the LM@CNC-PAM-CS hydrogel, the contact angles further decreased to 19.91° and 14.76°, confirming its synergistic effect in enhancing hydrophilicity. The abundant amide groups in PAM and the amino and hydroxyl groups in CS promote the formation of a stable hydration layer through extensive hydrogen bonding with surrounding water molecules. This hydration interface effectively inhibits the adsorption of non-specific proteins, thereby significantly improving the biosensor's anti-fouling capability.
[0048] As a major component of saliva, proteins readily adsorb onto electrode surfaces, hindering electron transfer and reducing current response, thereby further affecting the detection accuracy and stability of biosensors. Therefore, this invention selected several common proteins found in saliva to investigate the anti-fouling properties of the sensing surface. Electrodes with different surface modifications were exposed to solutions of BSA, lysine (Lys), mucin (Muc), and cellulose (Fib) at different concentrations for 30 minutes. Figure 4 As shown in BE, both the bare electrode and PEDOT / GCE exhibited high signal suppression rates within the protein concentration range, indicating severe protein adsorption on the electrode surface. Conversely, the hydrogel- and peptide-modified electrodes showed the lowest current suppression rates in each protein solution, demonstrating that the biosensor interface possesses stronger resistance to non-specific protein adsorption.
[0049] To further visually evaluate the protein adsorption, different surfaces were subjected to 0.2 mg / mL... -1 After incubation in FITC-BSA solution, the characterization was performed using laser scanning confocal microscopy, and the results are as follows: Figure 4As shown in Figure F, strong green fluorescence signals were observed on the GCE and PEDOT / GCE surfaces, indicating a large accumulation of FITC-BSA. In contrast, the LM@CNC-PAM-CS hydrogel and peptide-modified surfaces exhibited extremely weak fluorescence signals, confirming a significant reduction in protein adsorption. These observations are consistent with DPV measurements and can be attributed to the synergistic antifouling effect between the LM@CNC-PAM-CS hydrogel and the peptide: its abundant hydrophilic groups facilitate the formation of a stable hydration layer, effectively inhibiting the adsorption of non-specific proteins, further validating the excellent antifouling performance of this sensing interface.
[0050] Example 4: Antifouling characterization of the antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE in complex biological samples To examine the antifouling performance of the constructed biosensor in real biological fluids, DPV measurements were performed by immersing a series of saliva samples of different concentrations at different interfaces, and the current signal suppression rate was recorded. Figure 5 As shown in Figures AB, significant signal inhibition was observed on GCE and PEDOT / GCE, indicating that non-specific adsorption of saliva led to severe biocontamination; while the inhibition rate of the LM@CNC-PAM-CS / PEDOT / GCE hydrogel was reduced. Notably, after subsequent peptide modification, the degree of signal inhibition was significantly reduced, reaching only 7.5% and 6.8% in unstimulated and chewed saliva, respectively. This indicates that the synergistic anticontamination performance of the hydrogel and peptide modification effectively reduced the accumulation of biocontaminants at the detection interface, thereby ensuring reliable analytical performance in complex biological environments. To assess long-term anticontamination stability, both the LM@CNC-PAM-CS hydrogel and the peptide-modified electrode were continuously exposed to 50% human saliva and characterized by DPV (dispersive phosphometry). Figure 5 C). Compared with electrodes modified with hydrogel alone, the current signal suppression effect was better after further peptide modification. After 15 days of saliva exposure, the inhibition rate was approximately 10%, indicating that the synergistic effect of LM@CNC-PAM-CS hydrogel and peptide significantly improved the antifouling performance.
[0051] Example 5: Analytical performance of the anti-fouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE Before evaluating the sensing performance of the biosensor, key preparation parameters, including peptide concentration and IL-1β incubation time, were optimized to improve sensitivity and resistance to contamination. Subsequently, the DPV response of the prepared biosensor was monitored in PBS and 50% unstimulated saliva for quantification of IL-1β. Figure 6 As shown in A and 6B, at 1 pg mL -1Up to 1 μg mL -1 Within the IL-1β concentration range, the DPV response gradually decreases with increasing IL-1β concentration. Figure 6 C indicates that the change in current (ΔI) is linearly related to the logarithm of the IL-1β concentration. In PBS, the linear regression equation is ΔI(μA) = 5.08LgC + 20.47(R²). 2 =0.9974), and the limit of detection (LOD) calculated using the 3σ / σs standard is 0.34 pg mL. -1 Where σ and S represent the standard deviation and calibration slope of the blank signal, respectively, this value is significantly lower than that of previously reported IL-1β biosensors. Furthermore, based on the calibration curve in 50% unstimulated saliva, the LOD was estimated to be 0.39 pg / mL. -1 The curve fits the following linear equation: I(μA) = 5.22LgC + 21.92(R) 2 =0.99), confirming that the biosensor has reliable detection performance for quantitative analysis of IL-1β in actual saliva samples.
[0052] In clinical applications, biosensors must maintain high selectivity to accurately detect target substances. To further validate the selectivity of the biosensor, we exposed it to relatively high concentrations of various interfering proteins in saliva, including IL-6, cTnI, ANXA1, HER2, CRP, and Aβ. 1-42 .like Figure 6 As shown in Figure D, unlike the significant current signal changes in IL-1β and the mixed solution, the signal changes caused by these proteins are almost negligible, indicating that the biosensor has good selectivity for IL-1β. The stability of the biosensor is crucial for evaluating its reliability and practicality. Furthermore, to assess the reproducibility of the biosensor, the DPV response was observed using seven independently prepared biosensors. Figure 6 The E-display current response is almost identical, with a relative standard deviation of only 4.57%, which fully demonstrates its excellent repeatability.
[0053] Seven saliva samples were collected from volunteers to evaluate the clinical application value of the developed biosensor in detecting IL-1β and to compare the results with those obtained using a conventional ELISA kit. Figure 6 As shown in Figure F, the results indicate that the biosensor is in good agreement with the ELISA kit, demonstrating its excellent accuracy and reliability in monitoring IL-1β in saliva and its significant potential for diagnostic applications.
[0054] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An electrochemical sensor based on hydrogel and peptide synergistic antifouling, characterized in that, The electrochemical sensor is constructed through a stepwise assembly process. First, a poly(3,4-ethylenedioxythiophene) film is deposited on the surface of a glassy carbon electrode. Then, an LM@CNC-PAM-CS hydrogel suspension is drop-coated onto the poly(3,4-ethylenedioxythiophene) film to form a functionalized hydrogel interface. Finally, a peptide is coupled to the functionalized hydrogel interface to obtain the electrochemical sensor in which the hydrogel and peptide work synergistically to resist fouling.
2. The electrochemical sensor based on hydrogel and peptide synergistic antifouling as described in claim 1, characterized in that, The method for preparing the LM@CNC-PAM-CS hydrogel suspension is as follows: 100 mg of liquid metal was added to 2 mL of a 0.2 wt% aqueous solution of cellulose nanofibers, and the mixture was sonicated in an ice-water bath for 30 minutes to obtain a uniformly dispersed LM@CNC nanoparticle suspension. Subsequently, chitosan was dissolved in 1% acetic acid to prepare a 2 mg / mL solution. -1 The chitosan solution was prepared; then, 1.5 g of acrylamide was added to the LM@CNC nanoparticle suspension and sonicated for 20 minutes; then the prepared chitosan solution was added and sonicated for another 20 minutes to obtain the LM@CNC-PAM-CS hydrogel suspension. The liquid metal is composed of 75% Ga and 25% In.
3. The electrochemical sensor based on hydrogel and peptide synergistic antifouling as described in claim 1, characterized in that, The amino acid sequence of the polypeptide is: CPPPPKSESKSENFMQGTSYHHVY, wherein the anchoring sequence is CPPPP, the anti-pollution sequence is KSESKSE, and the specific recognition sequence for IL-1β is NFMQGTSYHHVY.
4. A method for preparing a hydrogel and peptide-based synergistic antifouling electrochemical sensor as described in claim 1, characterized in that, Includes the following steps: (1) Polish the glass carbon electrode with Al2O3 powder, and then use deionized water and anhydrous ethanol for ultrasonic cleaning to remove adsorbed impurities; (2) A poly(3,4-ethylenedioxythiophene) thin film was formed on the surface of a glassy carbon electrode by electrochemical deposition. (3) The LM@CNC-PAM-CS hydrogel suspension was drop-coated onto the surface of a poly(3,4-ethylenedioxythiophene) film and incubated to obtain an LM@CNC-PAM-CS hydrogel modified electrode. Then, it was immersed in PBS buffer to allow the hydrogel to fully swell to equilibrium and obtain a functionalized hydrogel interface. (4) The functionalized hydrogel interface was immersed in a solution of sulfosuccinimide-4-(N-maleimidemethyl)cyclohexane-1-carboxylic acid ester and reacted. After the reaction was completed, it was thoroughly washed with water to remove residual reagents. (5) Finally, a polypeptide solution was added to the washed interface surface and incubated to obtain the antifouling electrochemical sensor Pep / LM@CNC-PAM-CS / PEDOT / GCE, which is the hydrogel and polypeptide synergistic antifouling electrochemical sensor.
5. The method according to claim 4, characterized in that, The electrochemical deposition method described in step (2) to form a poly(3,4-ethylenedioxythiophene) film on the surface of a glassy carbon electrode is as follows: 5 mL of electrochemical polymerization solution containing 0.01 mg of poly(sodium 4-styrene sulfonate) and 10 mM 3,4-ethylenediol thiophene is prepared and deposited at 1.0 V in amperometric mode for 20 seconds to form a poly(3,4-ethylenedioxythiophene) film on the surface of the glassy carbon electrode.
6. The method according to claim 4, characterized in that, The amount of LM@CNC-PAM-CS hydrogel suspension used in step (3) is 3.0 μL; the incubation time is 2 h; The PBS buffer has a pH of 7.4 and a concentration of 10 mM.
7. The method according to claim 4, characterized in that, The amount of SMCC solution used in step (4) is 10 μL, the concentration is 2.0 mM, and the reaction time is 1 h.
8. The method according to claim 4, characterized in that, The amount of polypeptide solution used in step (5) is 10 μL, and the concentration is 0.2 mg / mL. -1 The incubation time is 2 hours.
9. An application of the hydrogel and peptide synergistic antifouling electrochemical sensor as described in any one of claims 1-3, or the hydrogel and peptide synergistic antifouling electrochemical sensor prepared by the method described in any one of claims 4-8.
10. The application according to claim 9, characterized in that, The specific application is the detection of IL-1β in complex biological environments.